2020
DOI: 10.1159/000505330
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Knowledge, Attitudes, and Practices of Patients and Families with Diagnoses of Hereditary Neuromuscular Disorders

Abstract: Background: Hereditary neuromuscular disorders (NMDs) result in progressive disability with no definitive disease modifying treatments. There is a delay in diagnosis, and lack of awareness among affected individuals about these disorders, which can affect quality of life of patients. Objective: The aim of this study is to identify gaps in patient knowledge, factors affecting attitudes toward the diagnoses, and specific practices to create better awareness among patients and healthcare providers to improve care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Most parents reported that understanding SMA was one of the difficulties faced after diagnosis confirmation. This difficulty was previously described not only by parents of individuals with SMA 13 but also by caregivers of children with Duchenne and Becker Muscular Dystrophy 14 and Autism Spectrum Disorder (ASD) 15 . Specifically regarding SMA, there is insufficient knowledge of its characteristics which can have consequences for the affected individuals and their families.…”
Section: Discussionmentioning
confidence: 89%
“…Most parents reported that understanding SMA was one of the difficulties faced after diagnosis confirmation. This difficulty was previously described not only by parents of individuals with SMA 13 but also by caregivers of children with Duchenne and Becker Muscular Dystrophy 14 and Autism Spectrum Disorder (ASD) 15 . Specifically regarding SMA, there is insufficient knowledge of its characteristics which can have consequences for the affected individuals and their families.…”
Section: Discussionmentioning
confidence: 89%
“…This evidenced by the diseases with initial psychological/behavioral issues later mingled with neurological ailments, reflecting and at the same time enforcing the basic need for understanding of the complete spectrum of the disease under neuropsychiatric conundrum. [46][47][48][49] Families with genetically triggered psychological issues have every chance of heralding neurological ailments and vice versa. An overlapping spectrum of neurological and psychiatric issues harboring several genetic correlations underneath, only visible by its finer sense, reflects the two sides of a similar disease conundrum.…”
Section: Social Contributions To the Genesis Of Difficult Understandi...mentioning
confidence: 99%
“…An overlapping spectrum of neurological and psychiatric issues harboring several genetic correlations underneath, only visible by its finer sense, reflects the two sides of a similar disease conundrum. [45][46][47][48][49]…”
Section: Social Contributions To the Genesis Of Difficult Understandi...mentioning
confidence: 99%
“…Thus, pediatricians and pediatric residents are expected to have detailed knowledge of diagnostic and management features of DMD in addition to the routine treatment options along with the natural course of the disease. The knowledge levels and attitudes towards the disease and coping strategies of the patients and parents on hereditary neuromuscular diseases have been subject to numerous studies (4)(5)(6). However, no study concerning the knowledge levels, attitudes, and practices of the medical doctors with the most frequent exposure to this diseasepediatricians and pediatric residents -could be found in the literature.…”
mentioning
confidence: 99%